2006
DOI: 10.1291/hypres.29.849
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan and Irbesartan Therapy in Type 2 Diabetic Patients Treated with Rosiglitazone: Effects on Insulin-Resistance, Leptin and Tumor Necrosis Factor-.ALPHA.

Abstract: The aim of our study was to investigate the metabolic effect of telmisartan and irbesartan in subjects treated with rosiglitazone, a well-known insulin-sensitizing drug, in order to clarify the direct metabolic effects of the two former drugs. Patients were enrolled, evaluated, and followed at 3 Italian centers. We evaluated 188

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 34 publications
3
41
0
13
Order By: Relevance
“…Further studies are needed to assess the effect of telmisartan on insulin resistance by hyperinsulinemic euglcyemic glucose clamp. It is noteworthy that other studies reported that telmisartan improves glycemic control and insulin sensitivity without affecting serum adi- (35)(36)(37). In rats fed a high-fat, high-carbohydrate diet, telmisartan treatment promoted increases in caloric expenditure and protected against dietary-induced weight gain (38).…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are needed to assess the effect of telmisartan on insulin resistance by hyperinsulinemic euglcyemic glucose clamp. It is noteworthy that other studies reported that telmisartan improves glycemic control and insulin sensitivity without affecting serum adi- (35)(36)(37). In rats fed a high-fat, high-carbohydrate diet, telmisartan treatment promoted increases in caloric expenditure and protected against dietary-induced weight gain (38).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, in a previous study comparing the effects of two different sartans (telmisartan and irbesartan) on adipokine levels, these effects actually did appear earlier with telmisartan than irbesartan. 40 Moreover, we did not evaluate the baseline distribution of adipose tissue in our patients, so we could not be sure that patients were equally distributed between the two treatment groups with regard to visceral adiposity. However, the patients were matched according to many anagraphic, clinical and metabolic parameters (including waist circumference and BMI), so we feel confident that the patients were adequately randomized.…”
Section: Discussionmentioning
confidence: 99%
“…Although designed to bind to the AT1R, a subset of ARBs that includes telmisartan has the potential to activate the insulin-sensitizing nuclear hormone receptor PPAR γ, completely independent from their AT1R blocking properties. [25][26][27] Benson, et al 27) showed that the potent PPAR γ -activating ARB telmisartan improved insulin sensitivity in rats fed a high-fat diet, whereas losartan had no effect. In addition, they showed that adiponectin expression in adipocytes and fat tissue was solely up-regulated by PPAR γ -activating ARBs, whereas non-PPAR-activating ARBs had no effect.…”
Section: Discussionmentioning
confidence: 99%